Genomic Overlap between Platelet Parameters Variability and Age at Onset of Parkinson Disease - Alfonsina Tirozzi; Roberta Parisi; Chiara Cerletti; Maria Benedetta Donati; Giovanni de Gaetano; Licia Iacoviello; Alessandro Gialluisi (Applied Sciences, 2021)
With the increasing burden of common neurodegenerative disorders and their long-hypothesized link with platelet biology, genomic approaches have been recently used to investigate the presence of a shared genetic basis between neurodegenerative risk and platelet parameters, reporting a significant though moderate genetic correlation between Parkinson Disease (PD) risk and platelet distribution width, an index of platelet size variability. Here, we investigated the genetic overlap of platelet parameters with an endophenotype of PD, age-at-onset (PD-AAO). First, we applied a Linkage Disequilibrium (LD)-score regression to the summary statistics of a large independent Genome Wide Association Study (GWAS) previously conducted, to estimate the co-heritability based on common genetic variants. Then, we analyzed multitrait single-variant associations to identify novel loci associated with both PD-AAO and mean platelet volume (MPV). Finally, we performed gene and gene-set enrichment analyses of these associations. We observed a statistically significant genetic correlation between MPV and PD-AAO (rg (SE) = −0.215 (0.082); p = 0.009). The multitrait analysis revealed eight novel variants associated with PD-AAO and 33 with MPV. The genes most significantly enriched for associations with PD-AAO included ARHGEF3 (Rho Guanine Nucleotide Exchange Factor 3), previously associated with depression, and KALRN (Kalirin RhoGEF Kinase), encoding a PINK1 interactor previously implicated in schizophrenia, Alzheimer Disease and PD itself. Interestingly, these genes were also identified in the analysis of MPV. The most significant gene-set enrichments shared between MPV and PD-AAO were observed for coagulation- and megakaryopoiesis-related pathways. These findings provide novel hints into the common genetic basis of PD endophenotypes, platelet biology and its neuropsychiatric comorbidities, paving the way for investigating common underlying mechanisms.